The embodiment of Qian Zhongshu's Guan Zhui Bian in an internet novel: Xuanxue and metaphor - Wang, Aiqing (Department of Applied Linguistics, FBSB, Universitas Negeri Yogyakarta, 2024)
As an iconic intellectual, novelist, translator and poet in the 20th century, é’±é’Ÿä¹¦ Qian Zhongshu (1910-1998) was not only celebrated for literary aptitude, epitomised by his chef-d'oeuvre å›´åŸŽ Wei Cheng